Reflexive Understanding of the Concept of a Spouse – Comments on the Impact of the Decision of the Court of Justice of the European Union in Coman and Others on the Rulings of Administrative Courts - Chmielarz-Grochal Anna; Wojciechowski Bartosz (Studies in Logic, Grammar and Rhetoric, 2023)
This article relates to the CJEU’s understanding of the concept of the spouse in Case C-673/16 and its effect on the process of law application by Polish administrative courts. The authors considerations are based on the assumption that the CJEU’s interpretation of EU law in Coman and Others is of a dynamic-deliberative nature, based on functional rules, and that at the same it time takes into account a specific legal and socio-cultural context in which one of the fundamental freedoms guaranteed by EU law is implemented. This judgment, as authors underline, confirms that a proper understanding of the current legal context of the concept of a spouse requires that the social and cultural context and the plurality of values arising from different lifestyles be taken into account in the application and interpretation of the law, all with a view to empowering the individual in his or her relationship with the State and raising the level of protection of human rights. Authors observe in the practice od Polish administrative courts that this CJEU’s judgment is important in the argumentative layer, but not decisive for the resolution of the case in specific situations where there is a need to address the effect of same-sex marriage in a case related to the implementation of the EU right to free movement. In this context authors consider whether the justification for rulings of administrative courts may be sought in John Gray’s concept of modus vivendi liberalism.